The Times are A-Changin': Metric Flexibility and Text Expression in 1960s and 1970s Singer-Songwriter Music. (13th November 2021) - Murphy, Nancy
Abstract: In 1960s and 1970s singer-songwriter music, some artists used a malleable approach to meter in performance that resulted in songs with extremes of self-expressive timing flexibility that cannot be accounted for by using a single conception of meter. As a solution, this article draws together theories of metric hierarchy, metrical reinterpretation, and metric process to develop the theory of flexible meter . This approach recasts meter as able to encompass the variety of metric scenarios presented by these singer-songwriters, from metric regularity to metric ambiguity and vacillations between these two possibilities. Performances by Bob Dylan, Joni Mitchell, Buffy Sainte-Marie, Paul Simon, and Cat Stevens are discussed to investigate their levels of engagement with meter—the degree to which their performances are regular or ambiguous—and how the individual metric style of each artist contributes to the self-expressive singer-songwriter performance practice.